Scaling Up From Regional Case Studies to a Global Harmful Algal Bloom Observing System - Anderson, Clarissa R.; Berdalet, Elisa; Kudela, Raphael M.; Cusack, Caroline K.; Silke, Joe; O’Rourke, Eleanor; Dugan, Darcy; McCammon, Molly; Newton, Jan A.; Moore, Stephanie K.; Paige, Kelli; Ruberg, Steve; et al. (Frontiers in Marine Science, 2019)
Harmful algal blooms (HABs) produce local impacts in nearly all freshwater and marine systems. They are a global problem that require integrated and coordinated scientific understanding leading to regional responses and solutions. Given that these natural phenomena will never be completely eliminated, improved scientific understanding of HAB dynamics coupled with monitoring and ocean observations facilitates new prediction and prevention strategies. Regional efforts are underway worldwide to create state-of-the-art HAB monitoring and forecasting tools, vulnerability assessments, and observing networks. In the United States, these include Alaska, Pacific Northwest, California, Gulf of Mexico, Gulf of Maine, Great Lakes, and the U.S. Caribbean islands. This paper examines several regional programs in the United States, European Union, and Asia and concludes that there is no one-size-fits-all approach. At the same time, successful programs require strong coordination with stakeholders and institutional sustainability to maintain and reinforce them with new automating technologies, wherever possible, to ensure integration of modelling efforts with multiple regional to national programs. Recommendations for scaling up to a global observing system for HABs can be summarized as follows: 1) advance and improve cost-effective and sustainable HAB forecast systems that address the HAB-risk warning requirements of key end-users at global and regional levels; 2) design programs that leverage and expand regional HAB observing systems to evaluate emerging technologies for Essential Ocean Variables (EOVs) and Essential Biodiversity Variables (EBVs) in order to support interregional technology comparisons and regional networks of observing capabilities; 3) fill the essential need for sustained, preferably automated, near real-time information from nearshore and offshore sites situated in HAB transport pathways to provide improved, advanced HAB warnings; 4) merge ecological knowledge and models with existing Earth System Modelling Frameworks to enhance end-to-end capabilities in forecasting and scenario-building; 5) provide seasonal to decadal forecasts to allow governments to plan, adapt to a changing marine environment, and ensure coastal industries are supported and sustained in the years ahead; and 6) support implementation of the recent calls for action by the United Nations Decade 2010 Sustainable Development Goals (SDGs) to develop indicators that are relevant to an effective and global HAB early warning system.